Comparison of stress and stress–strain approaches for the active contraction in a rat cardiac cycle model - Martonová, Denisa; Holz, David; Seufert, Julia; Duong, Minh Tuan; Alkassar, Muhannad; Leyendecker, Sigrid (Journal of Biomechanics, 2022)
In the last decades, different strategies to model the active electromechanically coupled behaviour of the cardiac tissue were proposed in order to simulate electromechanics of the heart under healthy and pathological conditions. The main objective of this work is to compare two approaches for modelling the active contraction during the electromechanically coupled rat cardiac cycle —- the stress and the stress–strain approach. Firstly, a cylindrical benchmark is considered and secondly, for a generic model of a rat left ventricle, a simulation including the Windkessel model, excitation via Purkinje fibre network and mechano-electrical feedback is performed. The model is calibrated with experimental data for rats, partly from own measurements via cardiac ultrasound, partly from the literature. Further, possibilities to reach higher ejection fractions are discussed and considered for an exemplary rat left ventricle. Within each approach, we observe regionally different active stresses and fibre stretches. Moreover, the transmural active stress and fibre stretch distribution is influenced by the pressure load on the endocardial surface. The active stress approach is not sensitive to the fibre stretch and transmurally varying fibre stretch in the left ventricular domain is observed. The active stress–strain approach leads to transmurally more homogeneous fibre stretch at the end-systolic state.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Active stress; Cardiac cycle; Cardiac electromechanics; Finite element method; Rat left ventricle